Level 2 Diploma in Electrical Installations 2365 : Buildings and structures units 201-204 and 210 - Deans, James L.; Harris, Paul, 1961-; Hay-Ellis, Andrew; Pickard, Trevor; City and Guilds of London Institute (London : City & Guilds, 2014)
This title provides all the information the reader will need to pass the City & Guilds level 2 diploma in electrical installations.
Includes index.
Formerly CIP.
Keywords: Electric wiring, Interior -- Handbooks, manuals, etc; Electric apparatus and appliances -- Installation -- Handbooks, manuals, etc